Nomograms for Predicting the Lymph Node Metastasis in Early Gastric Cancer by Gender: A Retrospective Multicentric Study - Sui, Wannian; Chen, Zhangming; Li, Chuanhong; Chen, Peifeng; Song, Kai; Wei, Zhijian; Liu, Hu; Hu, Jie; Han, Wenxiu (Frontiers in Oncology, 2021)
Background Lymph node metastasis (LNM) has a significant impact on the prognosis of patients with early gastric cancer (EGC). Our aim was to identify the independent risk factors for LNM and construct nomograms for male and female EGC patients, respectively. Methods Clinicopathological data of 1742 EGC patients who underwent radical gastrectomy and lymphadenectomy in the First, Second and Fourth Affiliated Hospital of Anhui Medical University between November 2011 and April 2021 were collected and analyzed retrospectively. Male and female patients from the First Affiliated Hospital of Anhui Medical University were assigned to training sets and them from the Second and Fourth Affiliated Hospital of Anhui Medical University were enrolled in validation sets. Based on independent risk factors for LNM in male and female EGC patients from the training sets, the nomograms were established respectively, which was also verified by internally validation from the training sets and externally validation from the validation sets. Results Tumor size (OR: 1.386, P=0.030), depth of invasion (OR: 0.306, P=0.001), Lauren type (OR: 2.816, P=0.000), LVI (OR: 0.160, P=0.000) and menopause (OR: 0.296, P=0.009) were independent risk factors for female EGC patients. And for male EGC patients, tumor size (OR:1.298, P=0.007), depth of invasion (OR:0.257, P=0.000), tumor location (OR:0.659, P=0.002), WHO type (OR:1.419, P=0.001), Lauren type (OR: 3.099, P=0.000) and LVI (OR:0.131, P=0.000) were independent risk factors. Moreover, nomograms were established to predict the risk of LNM for female and male EGC patients, respectively. The area under the ROC curve of nomograms for female and male training set were 87.7% (95%CI: 0.8397 - 0.914) and 94.8% (95%CI: 0.9273-0.9695), respectively. For the validation set, they were 92.4% (95%CI: 0.7979-1) and 93.4% (95%CI: 0.8928 - 0.9755) respectively. Additionally, the calibration curves showed good agreements between the bias-corrected prediction and the ideal reference line for both training sets and validation sets in female and male EGC patients. Conclusions Nomograms based on risk factors for LNM in male and female EGC patients may provide new insights into the selection of appropriate treatment methods.